83 Beta-hCG Positive Metastatic Cholangiocarcinoma in Liver Mimicking Pregnancy in a Young Woman. (11th January 2018) - Wong, Myra; Suo, Liye; Jain, Shilpa; Xu, Ya
Abstract: Introduction: Human chorionic gonadotropin B (beta-hCG) can be rarely expressed by non-trophoblastic tumors of the bladder, breast, lung, gastrointestinal tract, etc. We report a rare case of a young woman worked up for pregnancy due to elevated beta-hCG, incidentally revealed to have metastatic adenocarcinoma in the liver. Case Summary: A 39-year-old Hispanic woman presented with abdominal pain and positive urine pregnancy test. Serum beta-hCG was elevated at 127 mIU/mL and rose to 1, 081 mIU/mL in a month; however, no gestational sac was identified on imaging. CT showed multiple hypoechoic liver masses (the largest 4.2 cm in segment 8) and an irregularly thickened gallbladder wall, suggestive of a metastatic process. Tumor markers were unremarkable, and alkaline phosphatase was 856 U/L. Fine needle aspiration (FNA) and touch smears displayed clusters of neoplastic cells with intracytoplasmic vacuoles. Core biopsy showed a tumor composed of nests and cords of pleomorphic cells with intracytoplasmic mucin and rare glandular arrangement consistent with adenocarcinoma. The tumor was positive for CK7 and CK17, and negative for CK20, compatible with biliary origin. Beta-hCG immunostain showed positive cytoplasmic staining in the tumor cells, confirming the source of elevated serum beta-hCG. Discussion: Follow-up revealed that the liver mass rapidly increased in number and size with more prominent gallbladder circumferential mass and nodularity, leading to death of the patient a month later. Immunohistochemistry confirmed strongly and diffusely beta-hCG expression in primary or metastatic cholangiocarcinoma has rarely been reported. Conclusion: We describe an interesting case of cholangiocarcinoma with beta-hCG expression with a delay in diagnosis due to presumptive diagnosis of pregnancy in a young woman. Non-trophoblastic tumors should be considered in the differential diagnosis of a patient with elevated beta-hCG and no detectable pregnancy by imaging. Early treatment with chemotherapy has been reported to be beneficial in certain cases in the literature.